Radiological signs of «hidden» fracture-dislocations of elbow - Matelenok, Ievgen (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2015)
It is proved that there are fracture-dislocations of elbow leading to spontaneous reduction of the forearm. Due to this it is likely erroneous determination of injur y and therefore inadequate treatment with unsatisfactor y results. Objective: To identify significant radiological criteria which will make it possible to define injuries of the elbow as fracture-dislocation in case of absence of radiological picture of the forearm dislocation according to results of primary radiological examination. Methods: Among 95 patients with fracture-dislocation of elbow we identified main group of 16 patients whom during primar y X-ray examination was not fixed dislocation of the forearm in (all of them had fracture of the radial head). The control group included 46 patients with trivial fractures of the radial head. The results of radiological examination of elbows were analyzed patients in both groups. Results: There were found radiological signs allowing to consider the damage as «hidden»fracture-dislocation of elbow. In 53.8 % of the patients in the main group the radial head dislocation was set as well as its rotation to about 90° and location behind the capitulum of the humerus. In 46.2 % of the patients there were found rather large head pieces (about ½ of its size) which were shifted forward, laterally, or in anterolateral direction, and besides distance of displacement is compared with the value of the piece. Conclusions: The most distinctive feature for the «hidden»fracture-dislocations is the presence of large-sized fragments of the radial head or fragments of the other bone formation with a significant shift them back and rotation to about 90° or offset forward, laterally or anterolateral direction for distance comparable to the size of fragment. Probability of «hidden»fracture- dislocation of elbow is higher in cases of fractures of the radial head type III (according to Mason classification modified by M.A. Broberg, B.F. Morrey).